2017
DOI: 10.1038/srep42682
|View full text |Cite
|
Sign up to set email alerts
|

High-amplitude electrical stimulation can reduce elicited neuronal activity in visual prosthesis

Abstract: Retinal electrostimulation is promising a successful therapy to restore functional vision. However, a narrow stimulating current range exists between retinal neuron excitation and inhibition which may lead to misperformance of visual prostheses. As the conveyance of representation of complex visual scenes may require neighbouring electrodes to be activated simultaneously, electric field summation may contribute to reach this inhibitory threshold. This study used three approaches to assess the implications of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 54 publications
5
36
0
Order By: Relevance
“…. The overall resulting P 50 threshold was 5.24 ± 0.24 μC/cm 2 ( n = 5), which is lower ( P ‐value < 0.05) than those obtained from a feline model using a similar combination of intravenous and gaseous anesthesia …”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations
“…. The overall resulting P 50 threshold was 5.24 ± 0.24 μC/cm 2 ( n = 5), which is lower ( P ‐value < 0.05) than those obtained from a feline model using a similar combination of intravenous and gaseous anesthesia …”
Section: Resultsmentioning
confidence: 58%
“…The rat has a sufficiently large eye to implant an electrode array in a model of the disease. Acute procedures are however long and require extended periods of surgical anesthesia to maintain the animal and to ensure its well‐being over several hours or days . In light of the 3‐Rs principle (replacement, reduction, and refinement), this approach helps reduce the number of animals required during the investigation of retinal stimulation paradigms: With extended anesthetic protocols, more scientific questions can be attempted during a single trial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent years have also revealed an interesting observation known as the upper threshold phenomenon ( Figure 4B) in RGC activation, i.e., a drop of response efficacy instead of saturation when stimulus strength exceeds a certain amount. The upper thresholds phenomenon was first observed by Boinagrov et al (2012), and then reported again in several other studies (Barriga-Rivera et al, 2017;Guo et al, 2018;Kotsakidis et al, 2018;Meng et al, 2018). Meng et al (2018) found that 20/21 cells exhibited the upper threshold phenomenon when sufficiently high charge was injected.…”
Section: Recent Progress Electrical Stimulation Of Retinal Neuronsmentioning
confidence: 75%